Bivalent furostene carbamates as antiproliferative and antiinflammatory agents. Issue 194 (November 2019) - Pathak, Nandini; Fatima, Kaneez; Singh, Sneha; Mishra, Divya; Gupta, Amit Chand; Kumar, Yogesh; Chanda, Debabrata; Bawankule, D.U.; Shanker, Karuna; Khan, Feroz; Gupta, Atul; Luqman, Suaib; et al.
Graphical abstract: Carbamate derivative at C26 of furostene ring after opening spiroketal bond (F-ring) of diosgenin exhibits potent anticancer activity against breast Cancer. Highlights: C26-furostene carbamates have been prepared from Diosgenin. Carbamate 10, antiproliferative against TNBC (IC50 = 13.5 μM) induces apoptosis by activation of caspase pathway. Concomitant antiproliferative and antiinflammatory property as well is important. Efficacy: In-vivo anticancer activity 65.4% tumour reduction at 75 mg/kg dose. Safety: In-vivo acute toxicity- safe up to 300 mg/kg dose. Abstract: Breast cancer is the most prevalent cancer in women affecting about 12% of world's female population. It is a multifactorial disease, mostly invasive in nature. Diosgenin and related compounds are potent antiproliferative agents. Carbamate derivatives have been synthesized at C26 of furostene ring after opening spiroketal bond (F-ring) of diosgenin. Compound 10 possessed significant antiproliferative activity against human breast cancer cells by arresting the population at G1 phase of cell division cycle and induced apoptosis. Induction of apoptosis was observed through the caspase signalling cascade by activating caspase-3. Moreover, carbamate 10 exhibited moderate antiinflammatory activity by decreasing the expression of cytokines, TNF-α and IL-6 in LPS-induced inflammation in primary macrophage cells. Furthermore, compound 10 significantly reduced Ehrlich ascites carcinoma significantly in mice. It was well tolerated and safe in acute oral toxicity in Swiss albino mice. The concomitant anticancer and antiinflammatory properties of carbamate 10 are important and thus, can further be optimized for a better anti-breast cancer candidate.